2012
DOI: 10.1027/0227-5910/a000151
|View full text |Cite
|
Sign up to set email alerts
|

Callers’ Experiences of Contacting a National Suicide Prevention Helpline

Abstract: Background: Helplines are a significant phenomenon in the mixed economy of health and social care. Given the often anonymous and fleeting nature of caller contact, it is difficult to obtain data about their impact and how users perceive their value. This paper reports findings from an online survey of callers contacting Samaritans emotional support services. Aims: To explore the (self-reported) characteristics of callers using a national suicide prevention helpline and their reasons given for contacting the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
3
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 36 publications
(72 reference statements)
7
95
3
11
Order By: Relevance
“…The qualitative findings on which this paper is based are drawn from a substantial mixed methods study of Samaritans emotional support services ( Coveney et al 2012;Pollock et al 2010). Data were collected between March 2008 and May 2009. the study included over 200 hours of observation (covering all weekdays and shifts) of Samaritans' activities and branches across the UK and qualitative interviews with 66 volunteers.…”
Section: Methods and Datamentioning
confidence: 99%
“…The qualitative findings on which this paper is based are drawn from a substantial mixed methods study of Samaritans emotional support services ( Coveney et al 2012;Pollock et al 2010). Data were collected between March 2008 and May 2009. the study included over 200 hours of observation (covering all weekdays and shifts) of Samaritans' activities and branches across the UK and qualitative interviews with 66 volunteers.…”
Section: Methods and Datamentioning
confidence: 99%
“…Another limitation to be considered is the difficulty in assessing the characteristics of "suicidality", from the perspective both of users and of volunteers/raters (Pollock et al, 2012; Freedenthal, 2008). Qualitative evidence suggests that many users consider that there is a natural link between having mental health problems and being suicidal (Pollock et al 2010) and that some work up suicidal identities as a strategic way to appeal for support and help (Pollock et al, 2012; Horne and Wiggins, 2008). In doing so, they risk creating a significant blurring of the associations, interpretations and conclusions made by researchers on the positive impact of telephone services on suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out above, qualitative findings have indicated that a common understanding of the term does not exist among users and volunteers (Pollock et al, 2010(Pollock et al, , 2012. The answer to the question whether telephone service interventions have a positive impact on their suicidal users seems, therefore, to hinge on what is meant by the term suicidal.…”
Section: Summary Of Analysis and Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Trained volunteers who provide online and telephone counselling are a valuable source of emotional help for individuals in crisis (150). Crisis helplines, in particular, have gained international recognition for their important contribution in supporting people during suicidal crises (151).…”
Section: Trained Volunteersmentioning
confidence: 99%